Compras públicas sustentáveis: uma análise sob a ótica da teoria da prática numa instituição pública de ensino superior - Silva, Aline Alves da (2024)
Sustainable Public Procurement (CPS) is the inclusion of sustainable criteria in the processes of contracting goods and services, emerging as a relevant public policy to promote economy, social justice and environmental preservation, especially in Brazil, where they represent a significant portion of annual GDP. In this scenario, universities are included, highlighted by different authors as essential for the promotion of sustainable development, as they play a crucial role in the training of professionals, in the propagation of knowledge, in the promotion of research on the topic of sustainability and in the promotion of actions aimed at sustainability. In this context, the present research proposed as a general objective to understand how sustainable public purchasing practices are configured at the University of International Integration of Afro-Brazilian Lusofonia (Unilab). The methodology adopted consisted of a case study in the Coordination of Tenders, Contracts and Equity (CLCP) at Unilab, with a qualitative approach and using the Theory of Practice by the authors Shove, Pantzar and Watson (2012), who consider practice as a behavior routinized composed of material elements, competencies and interdependent meanings. Data triangulation was used, according to Yin (2001), through: documentary analysis of files and other official documents made available relating to Unilab's sustainable purchasing process; interviews with 11 CLCP employees directly involved in some of the stages of the purchasing process, using a semi-structured script of questions; and direct observation, focusing on the actions of those involved in the practice of sustainable purchasing and documented through photos, videos and notes in a field diary. The collected data was processed and analyzed using the content analysis method (Bardin, 2011), to critically understand the data and categorize the content, with categories supported by the Theory of Practice framework of Shove, Pantzar and Watson (2012). The results revealed that the flow of Sustainable Public Procurement at Unilab follows a structure based on the division of work between the CLCP subunits. Furthermore, the constituent elements of these practices were identified, with the material consisting of objects, software and infrastructure; competence encompassing embodied knowledge and skills; and meaning by personal identification, importance of work and rational use of public resources. Unilab's Sustainable Public Procurement practices are aligned with the regulations and principles of the Brazilian legal system and have demonstrated the potential to contribute to sustainability, minimizing environmental impact and encouraging the local market to supply sustainable products. However, the interviewees considered that these practices are still superficial, possibly due to the absence of a strategic sector responsible for planning, coordinating, executing and monitoring initiatives that promote sustainable management in public procurement, aligned with the economic, social and environmental dimensions. It was also noted the absence of a Sustainable Logistics Master Plan (PLS) and the exclusive dependence on the Annual Contracting Plan (PCA) in which limitations to the effective promotion of sustainability in the institution's public purchasing practices are identified.